DNA FINGERINTS OF TILAPIA SPECIES IN SHATT AL-AREB RIVER USING RAPD MARKERS - & et al., Faddagh (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
In the last decade, tilapia fish species distributed in the Iraqi inland waters. Three species; Nile tilapia Oreochromis niloticus (Linnaeus, 1758), Blue tilapia Oreochromis aureus (Steindachner, 1864) and Redbelly tilapia Coptedon zillii (Gervais, 1848) inhibiting Shatt Al-Arab River. They belong to family Cichlidae. They are very similar to differentiate among them using biometry. So, genetic markers used for species discrimination. Randomly amplified polymorphic DNA (RAPD) protocol used to examine genetic variation and to generate DNA fingerprints of tilapia fish species in Shatt Al-Arab River. Sixty-two specimens of tilapia fish collected from Shatt Al-Arab River at the governorate of Basrah. Seven universal decamer primers selected (OPA08, OPA10, OPA13, OPA17, OPA19, OPB08 and OPC02) to create RAPD DNA fingerprint. RAPD-PCR amplification carried out and electrophoresed with 100 bp ladder. DNA bands scored and molecular weight was calculated using PhotocaptMW software. Analog histogram drew using MS-Excel. The three RAPD DNA profiles apparently were different. DNA bands scored in the three species were 67 bands. The size of DNA bands was ranged from 64 bp to 2344 bp. RAPD fingerprints were efficient to distinguish the three species of tilapia fish.  DNA markers of the three species of tilapia fish can use to achieve conservation programs of fish species in the future.